Evaluating support service co-operation in the Netcare-Settlers public private partnership, Grahamstown, South Africa - Mahote, Tulisa (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
The neo-liberal restructuring of state assets and facilities, which has taken place internationally over the past three decades, as well as in South Africa, has been a matter of great controversy. Privatisation, in particular, has been a polarising issue, especially when applied to fields like healthcare. Supporters of privatisation view it as cutting costs, mobilising funding, expertise and innovation, resulting in improved delivery, and opening possibilities for a spread of ownership. Critics claim the process involves retrenchments, declining services for the (poorer) majority of people, and a focus on the elites as citizens become transformed into customers, and with any economic empowerment going to the already prosperous. This thesis examines these issues by looking at the privatisation of hospitals in South Africa, with a case study of the Netcare-Settlers Public Private Partnership (PPP) (also known as the Settlers Private Hospital) in Grahamstown, South Africa. Netcare is South Africa's largest private hospital company, and also has substantial operations in the United Kingdom. The thesis sets out the context: a highly inequitable healthcare system in the country, the rise of privatisation in the apartheid and post-apartheid eras, and healthcare privatisation. In terms of the Netcare-Settlers PPP, the thesis examines how the PPP was structured and developed, focusing on the impact of the PPP on non-clinical operations. The thesis argues that the results of the PPP are mixed, that it has greatly improved areas like facilities, maintenance, cleaning and catering, performed less well in increasing the doctor/ patient ratio or in attracting specialists, and is associated with the widespread and problematic use of outsourcing of service workers like cleaners and security. Overall, the PPP has improved healthcare, with some effective sharing of resources between the public and private parts of the hospital, but also relies on a pool of relatively low waged, under-unionised, labour. In terms of the general debate over privatisation, the Netcare-Settlers PPP shows that both supporters and critics have some valid points, and that privatisation in practice is not an either/ or, black/ white, good/ bad proposition, but something more complex. The success and failure of PPPs depend on the details of the contracts, and these can be used to maximise the performance of both the public and private partners. Better contracts may help avoid the uneven results seen at institutions like the Netcare-Settlers PPP.
Keywords: Settlers Hospital; Netcare 911; Public-private sector cooperation -- South Africa -- Grahamstown; Privatization -- South Africa; Medical care -- Privatization -- South Africa; Health services accessibility -- South Africa; Contracting out -- South Africa